2021
DOI: 10.1111/php.13417
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of 810 nm Diode Laser Treatment in Periodontitis as an Alternative to Surgical Debridement Approach

Abstract: The efficacy of surgical periodontal may be compromised by inadequate patients' self-performed plaque control or lack of supportive periodontal therapy. This clinical case report aimed to evaluate the effectiveness of 810 nm diode laser-assisted full-mouth sulcular debridement, as a potential treatment modality in the management of chronic periodontitis along with a 12-month follow-up evaluation. Each periodontal pocket was lased within 2 mm of deepest point, using a light contact of "hot tip" of the fiber wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Inside the periodontal pocket for non-surgical therapy, we use a diode near-infrared laser with a wavelength between 800nm-980nm for coagulating gingivae (epithelial ablation inside the pocket) as an adjunct to SRP. Additionally, it results in complete removal of the inflamed epithelium and decreases the amount of pro-inflammatory agents [9,12,[28][29][30][31][32][33][34][35][36]. Appropriate laser wavelengths, with suitable protocols, probably can improve the periodontal status for a more extended period and likely limit the use of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inside the periodontal pocket for non-surgical therapy, we use a diode near-infrared laser with a wavelength between 800nm-980nm for coagulating gingivae (epithelial ablation inside the pocket) as an adjunct to SRP. Additionally, it results in complete removal of the inflamed epithelium and decreases the amount of pro-inflammatory agents [9,12,[28][29][30][31][32][33][34][35][36]. Appropriate laser wavelengths, with suitable protocols, probably can improve the periodontal status for a more extended period and likely limit the use of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…These wavelengths generate a photothermal phenomenon with ablation and additionally haemostasis due to microvessels construction inside the pocket. Some part of the light is absorbed superficially, but some are reemitted as longer wavelengths with more superficial penetration, which causes the complete removal of the contaminated by intracellular periodontal pathogens gingival epithelium [32,34,37,[45][46][47][48][49].…”
Section: Tablementioning
confidence: 99%
“…which has been shown to reduce the formation of abnormal blood vessels and bleeding, thereby preserving gingival health.The results of the present study illustrated statistically significant positive treatment outcomes in terms of CAL gain and reduction in PPD at 3 and 6 months follow up in both the groups however significantly greater reduction in PPD and CAL were observed in the IG-PDT group. Recent studies reported a significant improvement in periodontal parameters using IG-PDT compared to scaling and root planning[32,35,39,44]. IG-PDT may convey anti-inflammatory properties and is effective in eliminating periodontal pathogens.…”
mentioning
confidence: 99%